Learning and action for gender-transformative climate-smart agriculture - Huyer, Sophia; Gumucio, Tatiana; Chanana, Nitya; Cramer, Laura K.; Mungai, Catherine; Ouédraogo, Mathieu; Simelton, Elisabeth; Tavenner, Katie; Twyman, Jennifer (2019)
This paper reports on a networking meeting of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Gender and Social Inclusion (GSI) Flagship held at the university of Canberra, Australia on 1-2 April 2019. The meeting helped to identify opportunities for gender-transformative, climate-smart agriculture (CSA) through knowledge sharing and next steps for CCAFS Phase Two. Researchers involved in gender and social inclusion working across CCAFS reviewed the existing knowledge base, noted key gaps, and began the process of identifying future research questions and themes.